Teacher Talk in Teaching Speaking of English Classroom Interaction Based on Foreign Language Interaction System - Khairani Hapshah Panggabean; Neni Afrida Sari Harahap (Universitas Negeri Medan, 2023)
This research is aimed at analyzing the categories of teacher talk in teaching speaking of English classroom interaction based on the FLINT system at grade VIII SMPIT Al-Hijrah Deli Serdang and explaining why teachers realize the categories of teacher talk as the way they do. The research design of this study was qualitative. The data were taken by recording and interviewing the teachers. FLINT system was used to analyze the data that contained eleven categories of teacher talk, namely: deals with feeling, praises or encourages, jokes, uses ideas of student, repeats student response verbatim, asks questions, gives information, corrects without rejection, gives direction, criticizes student behavior, and criticizes student response. The results showed that teacher 1 not applied corrects without rejection while teaching. Meanwhile, teacher 2 not applied jokes and repeats student response verbatim. The most significant difference between the two teachers was the class atmosphere taught by the first teacher was more cheerful than the second teacher. Then, the reasons teachers realize teacher talk categories are because of positive feeling atmosphere, increasing students' enthusiasm, creating a humorous class, developing ideas, emphasizing the words, providing the opportunity to speak, conveying information, building students' awareness, achieving the goals, changing students' non-acceptable behavior, and responding properly.